Peran Pemimpin Agama Dalam Membangun Harmoni Keagamaan Studi Kasus Desa Kesamben - Syihab, Azhar Saaidin; Widyastuti Herawati, Yayuk; Zuhri Adi Brata, Hilmi (Jurnal Makkareso, 2024)
This research aims to examine the role of religious leaders in building religious harmony in Kesamben Village. Kesamben Village was chosen as a case study because it is representative of a multi-religious community. The research method employed is qualitative with a case study approach. Data were collected through interviews, observations, and document analysis. The results of the research indicate that religious leaders play a key role in creating and maintaining religious harmony in Kesamben Village. They serve not only as religious figures but also as mediators, educators, and social cohesion agents within the community. Religious leaders help understand religious differences, promote tolerance, and facilitate interfaith dialogue. Therefore, this research contributes to the understanding of the vital role of religious leaders in the context of religious harmony.